Ambient NO2 adsorption removal by Mg–Al layered double hydroxides and derived mixed metal oxides. (1st September 2021) - Hanif, Aamir; Sun, Mingzhe; Wang, Tianqi; Shang, Shanshan; Tsang, Daniel C.W.; Shang, Jin
Abstract: NO2 is a potent air pollutant because of its deleterious effects on human beings and other organisms. The state-of-the-art catalysis-based deNOx techniques (e.g., selective catalytic/non-catalytic reduction) are incapable of ambient NO2 abatement due to their low efficiency at temperatures below 300 °C. It is thus conceivable to directly capture NO2 from the atmosphere by selective adsorption on porous materials. This work reports the rational development and demonstration of the Mg–Al layered double hydroxides (LDHs) and their derived mixed metal oxides (MMO), using environmentally benign solvents, as high-capacity adsorbents for ambient NO2 abatement. By boosting the densities of accessible basic sites using layer delamination strategies, the highest NO2 adsorption capacity of 8.52 mmol/g was achieved by the delaminated LDH material (LDH-AM), which was substantially higher than other popular and robust adsorbents, such as zeolites (0.36–3 mmol/g) and carbon-based adsorbents (2–6 mmol/g). Using Fourier transform infrared spectroscopy and powder X-ray diffraction, it was revealed that NO2 adsorption occurs on the surface M-OH basic sites and within the layers by simultaneously replacing the interlayer CO3 2− ions of LDH. This work affords not only promising, durable, and scalable adsorbents for ambient NO2 removal but also a strategy to develop adsorbents with high density of basic sites for capture of other pollutant acid gases from the environment. Graphical abstract: Image 1 Highlights: Structure-controlled base site density was exploited for NO2 adsorption. Base site density of layered double hydroxides was altered by different strategies. Both calcination and exfoliation led to enhanced NO2 adsorption capacity. Exfoliation is a better strategy than calcination for improving NO2 adsorption. The highest NO2 adsorption capacity of 8.52 mmol/g adsorbent was observed.